Iron-containing nitric acid waste liquid and method for recycling thereof
Patent Information
- Application Number
- CN202611102538.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-13
AI Technical Summary
公开号为CN117964063A的中国专利公开了一种从不锈钢酸洗废液中回收硝酸/氢氟酸的方法,其背景部分指出不锈钢酸洗废液中硝酸盐、铁盐和络合态组分并存,传统中和沉淀会产生污泥或高盐废水;公开号为CN110776139A的中国专利公开了一种扩散渗析钢铁酸洗废酸回收装置及方法,但其重点在装置流道和清洗结构,未针对非对称复合阴离子交换膜中支撑层、活性层和无机选择界面层之间的结构完整性与选择分离能力协同进行限定
1.本发明以聚偏二氟乙烯多孔支撑层作为膜体基础,通过孔径和厚度控制为扩散渗析提供稳定液体通道,同时避免单纯致密化支撑造成的传质阻力增加,使膜在含铁硝酸废液运行环境中保持较好的结构完整性和酸迁移适应性。
Smart Images

Figure CN122897484A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of waste acid membrane separation and resource recovery, specifically to an iron-containing nitric acid waste liquid and its recovery and reuse method. Background Technology
[0002] Metal pickling, chemical polishing, metal etching, and wet leaching are widely used for surface treatment or component conversion of steel, stainless steel, copper alloys, electronic metal parts, and intermediate materials in hydrometallurgy. These processes typically require a nitric acid system to provide oxidizing and dissolving power. During treatment, iron from the metal matrix, oxide scale, or leaching products can enter the acid solution, making the wastewater highly acidic, with high iron salt content and high corrosiveness. Direct neutralization of such wastewater not only consumes a large amount of alkali but also generates iron-containing sludge or high-salt wastewater, increasing the burden of subsequent disposal. Industrially, there is a greater desire to selectively recover free nitric acid from iron-containing systems without significantly increasing energy and reagent consumption, and to retain iron ions in the enrichment solution for resource recovery. Therefore, establishing a separation system for iron-containing nitric acid wastewater that combines acid recovery capacity, iron retention capacity, membrane stability, and adaptability for continuous operation is of great significance for reducing waste acid emissions, reducing hazardous waste generation, and improving the recycling level of metal surface treatment processes.
[0003] Existing diffusion dialysis studies have shown that anion exchange membranes can utilize concentration gradients to drive acid anion migration and achieve acid-metal salt separation by leveraging the repulsion of metal cations by positively charged groups within the membrane. However, constraints still exist between acid permeation, metal rejection, and membrane stability. Public reviews also indicate that diffusion dialysis has advantages such as low energy consumption and simple operation in acidic wastewater recovery, while the acid permeability, selectivity, and stability of the membrane directly affect the recovery effect. Chinese patent CN117964063A discloses a method for recovering nitric acid / hydrofluoric acid from stainless steel pickling wastewater. Its background section points out that nitrates, iron salts, and complexed components coexist in stainless steel pickling wastewater, and traditional neutralization and precipitation will produce sludge or high-salt wastewater. Chinese patent CN110776139A discloses a diffusion dialysis device and method for recovering acid from steel pickling wastewater, but its focus is on the device's flow channels and cleaning structure, without addressing the structural integrity and synergistic selective separation capabilities between the support layer, active layer, and inorganic selective interface layer in the asymmetric composite anion exchange membrane. Summary of the Invention
[0004] The purpose of this invention is to provide an iron-containing nitric acid waste liquid and its recycling and reuse method, which solves the pain point problem of difficulty in simultaneously achieving acid recovery selectivity and membrane structure stability, active layer processing controllability and ion exchange capacity in iron-containing nitric acid waste liquid.
[0005] This invention maintains membrane strength and liquid channels through a porous polyvinylidene fluoride support layer, provides anion migration capability through a cross-linked quaternized aromatic polymer layer, and forms a zirconium phosphate selective interface layer in situ on its outer surface. These measures respectively alleviate the problems of limited mass transfer caused by simply increasing the density of the support layer and insufficient structural stability caused by simply constructing an ultrathin selective layer, thereby achieving a synergistic unity of acid migration, iron retention and continuous operation stability in iron-containing nitric acid systems.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A waste liquid containing iron nitric acid, wherein the waste liquid is generated from metal pickling, chemical polishing, metal etching, or wet leaching processes, and comprises free nitric acid, dissolved iron ions, and water, wherein the mass fraction of the free nitric acid is 3-25 wt%, the total iron concentration (calculated as Fe) is 10-150 g / L, and the dissolved iron ions are Fe... 3+ and / or Fe 2+ .
[0007] A method for recycling and reusing iron-containing nitric acid wastewater, wherein the iron-containing nitric acid wastewater is wastewater generated from metal pickling, chemical polishing, metal etching, or wet leaching processes, containing free nitric acid, dissolved iron ions, and water. The free nitric acid has a mass fraction of 3-25 wt%, the total iron concentration (calculated as Fe) is 10-150 g / L, and the dissolved iron ions are Fe... 3+ and / or Fe 2+ This includes the following steps: S1. Provide the iron-containing nitric acid waste liquid as the feed liquid; S2. Use deionized water or an aqueous solution of nitric acid with an initial nitric acid mass fraction of 0.1-5.0 wt% as the receiving liquid; S3. The feed liquid and the receiving liquid are respectively introduced into both sides of the diffusion dialysis unit, and diffusion dialysis is carried out under the conditions of 20-45℃, feed liquid to receiving liquid volume flow ratio of 1:0.8 to 1:1.2, and transmembrane pressure difference not greater than 0.05MPa to obtain recovered acid solution and iron enrichment solution. The diffusion dialysis unit is equipped with an asymmetric composite anion exchange membrane, which includes a porous support layer made of polyvinylidene fluoride, an anion exchange active layer formed on one side of the porous support layer, and a zirconium phosphate selective interface layer formed on the outer surface of the anion exchange active layer. During diffusion dialysis operation, the zirconium phosphate selective interface layer faces the feed liquid side, and the porous support layer faces the receiving liquid side. The anion exchange active layer is a cross-linked quaternized aromatic polymer layer obtained by polymerizing 4-vinylbenzyl chloride with divinylbenzene and then quaternizing it with trimethylamine. The zirconium phosphate selective interface layer is formed by the in-situ reaction of zirconium oxychloride octahydrate and phosphoric acid on the outer surface of the anion exchange active layer. The porous support layer has an average pore size of 20-150 nm and a thickness of 45-170 μm, the anion exchange active layer has a thickness of 0.3-1.5 μm, and the ion exchange capacity based on the two-layer composite dry membrane system with completed trimethylamine quaternization and no zirconium phosphate selective interface layer is 0.8-1.8 mmol / g, and the zirconium phosphate selective interface layer has a thickness of 20-120 nm. S4. The recovered acid solution is returned to the acid preparation process for reuse, and the iron enrichment solution is used as a raw material for subsequent iron resource utilization treatment.
[0008] In this invention, the volumetric flow rate ratio of the feed liquid to the receiving liquid is the ratio of the volumetric flow rate of the feed liquid side to the volumetric flow rate of the receiving liquid side in the diffusion dialysis unit; when expressed as the receiving liquid / feed liquid volumetric flow rate ratio, its value is the receiving liquid side volumetric flow rate divided by the feed liquid side volumetric flow rate. The recovered acid solution is the effluent or circulating liquid collected from the receiving liquid side after a set operating time, and the iron enrichment solution is the effluent or circulating liquid collected from the feed liquid side after a set operating time.
[0009] In this invention, the zirconium phosphate selective interface layer refers to a zirconium-containing phosphate interface layer formed by the reaction of zirconium-containing precursors and phosphoric acid on the outer surface of anion exchange active layer, containing both Zr and P elements and with the compositional aperture limited by the Zr / P atomic ratio. The zirconium-containing phosphate interface layer can be in an amorphous or microcrystalline state, and is not necessarily limited to a single crystal phase.
[0010] Furthermore, the porous support layer is prepared through the following steps: A1. Based on a total of 100 parts by weight of polyvinylidene fluoride and N-methylpyrrolidone, add 15-25 parts by weight of polyvinylidene fluoride to 75-85 parts by weight of N-methylpyrrolidone, and mechanically stir at 300-500 rpm for 4-10 hours at 50-70°C to obtain a uniform casting solution without visible particles. A2. The casting solution is coated into a film with a wet film thickness of 100-250 μm, and after standing at 15-35℃ for 10-120s, it is immersed in deionized water at 5-25℃ for 10-30min for phase inversion. A3. Wash with deionized water until the residual amount of N-methylpyrrolidone in the membrane formed by phase transformation is no more than 0.5 wt%, and then dry at 40-70°C for 2-10 h to obtain the porous support layer with a porosity of 40-75 vol%.
[0011] Furthermore, the cross-linked chloromethyl precursor layer of the anion exchange active layer is prepared by the following steps: B1. Using the porous support layer as a substrate, 10-40 parts by weight of 4-vinylbenzyl chloride, 0.5-8 parts by weight of divinylbenzene, 0.1-2 parts by weight of 2,2'-azobisisobutyronitrile and 20-60 parts by weight of N-methylpyrrolidone are formulated into a precursor solution, which is then coated on one side of the porous support layer. B2. Under nitrogen protection, the reaction is carried out at 60-80℃ for 1-4 hours to polymerize the 4-vinylbenzyl chloride and the divinylbenzene in situ. B3. Wash with N-methylpyrrolidone and deionized water 1-3 times in sequence to obtain the crosslinked chloromethyl precursor layer with a mass increment of 5-25% relative to the porous support layer.
[0012] Furthermore, the anion exchange active layer is prepared by the following steps: C1. The cross-linked chloromethyl precursor layer is contacted with a 20-35 wt% trimethylamine aqueous solution and reacted at 20-40°C for 2-12 hours. C2. Wash with deionized water until the pH of the washing solution on the membrane surface is 6-8; C3. Dry at 30-60℃ for 1-6 hours to obtain the anion exchange active layer with a water content of 10-45wt%, an ion exchange capacity of 0.8-1.8mmol / g and a thickness of 0.3-1.5μm based on a two-layer composite dry membrane consisting of a PVDF porous support layer and a cross-linked quaternized aromatic polymer layer.
[0013] Furthermore, the zirconium phosphate selective interface layer is prepared through the following steps: D1. Contact the outer surface of the anion exchange active layer with an aqueous solution of zirconium oxychloride octahydrate with a concentration of 0.02-0.20 mol / L for 1-15 min in a one-sided contact manner; D2. Then, the outer surface is brought into contact with a 0.05-0.50 mol / L phosphoric acid aqueous solution for 5-60 minutes in a single-sided contact manner; D3. Wash with deionized water and dry at 25-50℃ for 0.5-4h to obtain the zirconium phosphate selective interface layer with a loading of 0.05-0.50mg / cm², a thickness of 20-120nm, and a Zr / P atomic ratio of 0.6-1.4.
[0014] In step D1, when the zirconium oxychloride octahydrate aqueous solution comes into contact with the outer surface of the anion exchange active layer, zirconium-containing species enter the near-surface hydration region of the cross-linked quaternized aromatic polymer layer and form a zirconium-containing precursor distribution region. This step uses the near-surface confined distribution as the precursor state for subsequent phosphoric acid treatment, and does not require simple electrostatic adsorption between the zirconium-containing species and the quaternary ammonium positive charge. In step D2, the phosphoric acid aqueous solution comes into contact with the zirconium-containing precursor distribution region and forms a zirconium- and phosphorus-containing interfacial component. Both steps D1 and D2 use the outer surface of the anion exchange active layer as the contact object, so that the zirconium phosphate selective interface layer is mainly formed on the feed liquid side surface.
[0015] Furthermore, at least one of the following conditions must be met: The dissolved iron ions include Fe 3+ and Fe 2+ And Fe calculated as Fe 3+ Concentration greater than Fe based on Fe 2+ concentration; The iron-containing nitric acid waste liquid originates from the stainless steel pickling process or the metal chemical polishing process.
[0016] Furthermore, it includes at least one of the following operations: In step S1, the iron-containing nitric acid waste liquid undergoes solid-liquid separation before entering the diffusion dialysis unit. The solid-liquid separation is performed using filtration with a pore size of 1-50 μm, and the suspended solids content in the feed liquid after filtration is less than 1 wt%. In step S3, the feed liquid and the receiving liquid pass through the diffusion dialysis unit in a countercurrent manner, and the linear velocities on both sides are 0.03-0.12 m / s.
[0017] Furthermore, the mass fraction of free nitric acid in the recovered acid solution is 5-20 wt%, and the total iron concentration, calculated as Fe, is not greater than 10 g / L.
[0018] Furthermore, after continuous operation for 8-72 hours, the diffusion dialysis unit is flushed online for 0.2-2 hours with deionized water or a nitric acid aqueous solution with a mass fraction of 0.1-5.0 wt%.
[0019] Furthermore, the iron-enriched liquid is further concentrated by evaporation or hydrolyzed by hot water and then used to prepare iron resource products.
[0020] As a concept of this invention, the present invention employs a design for iron-containing nitric acid wastewater with limited source composition and iron ion form, primarily aimed at achieving a synergistic balance between the identifiability of the wastewater composition and the suitability for subsequent selective separation. Existing treatment approaches, if focusing only on the recovery of acidic components, often neglect the impact of differences in iron ion valence state and source on membrane fouling, metal migration, and residual liquid disposal. Conversely, if focusing only on iron ion removal, the reuse value of nitric acid is easily sacrificed through neutralization and precipitation. This invention addresses the issue of free nitric acid, total iron concentration, and Fe... 3+ and Fe 2+ The combined limitations of form and waste liquid source enable the treatment target to cover typical metal surface treatment waste liquids, and provide clear boundaries for acid migration and iron enrichment during diffusion dialysis. This reduces the side effects caused by simple acid recovery or simple iron removal pathways, and provides a stable target basis for subsequent acid recovery and reuse and iron enrichment liquid resource utilization.
[0021] Furthermore, when installing the asymmetric composite anion exchange membrane in the diffusion dialysis unit, the zirconium phosphate selective interface layer faces the feed liquid side, and the porous support layer faces the receiving liquid side. The iron-containing nitric acid waste liquid, which serves as the feed liquid, first contacts the zirconium phosphate selective interface layer and then passes through the anion exchange active layer. The receiving liquid flows on one side of the porous support layer. After the membrane is installed, the membrane surface orientation on the feed liquid side and the receiving liquid side is recorded, and this installation state is used for diffusion dialysis operation.
[0022] Furthermore, during the preparation of the porous support layer, the casting solution was coated into films with wet film thicknesses of 100 μm and 250 μm, respectively. After phase inversion, washing, and drying, porous support layer samples were obtained. The dry film thickness of the porous support layer samples was measured, and a correspondence was established between the dry film thickness measurement value and the corresponding wet film thickness to determine whether the thickness of the porous support layer obtained after phase inversion is within the range of 45-170 μm.
[0023] Furthermore, the mass increment of the cross-linked chloromethyl precursor layer is calculated based on the dry weight of the same membrane before and after treatment. The dry weight of the porous support layer is denoted as m0, and the dry weight of the cross-linked chloromethyl precursor layer after in-situ polymerization of 4-vinylbenzyl chloride and divinylbenzene, cleaning and drying is denoted as m1. The mass increment is calculated by subtracting m0 from m1, dividing by m0 and then multiplying by 100%. The obtained mass increment is used to determine whether the mass increment of the cross-linked chloromethyl precursor layer relative to the porous support layer is 5-25%.
[0024] Furthermore, in preparing the anion exchange active layer, the cross-linked chloromethyl precursor layer is placed in a sealed container and completely immersed in a 20-35 wt% trimethylamine aqueous solution. The reaction is carried out at 20-40°C for 2-12 hours. After the reaction, the membrane is removed and washed with deionized water until the pH of the washing solution on the membrane surface is 6-8. Then, it is dried at 30-60°C for 1-6 hours to obtain the anion exchange active layer used for the subsequent preparation of the zirconium phosphate selective interface layer.
[0025] Furthermore, the ion exchange capacity was measured using membrane samples that had undergone trimethylamine quaternization without forming a zirconium phosphate selective interface layer and composite membrane samples that had undergone zirconium phosphate selective interface layer preparation, respectively. The amount of exchangeable anions in the test samples was determined using the chloride ion exchange capacity method. The mass of the test samples, the volume of the exchange solution, the concentration of the titrant, and the volume consumed at the titration endpoint were recorded. The ion exchange capacity was calculated based on the number of millimoles of exchangeable ions per gram of dry membrane. The 0.8-1.8 mmol / g ion exchange capacity used to characterize the anion exchange active layer was based on the dry membrane of the two-layer composite system that had undergone trimethylamine quaternization without forming a zirconium phosphate selective interface layer. The ion exchange capacity of the composite membrane sample after the zirconium phosphate selective interface layer preparation was used to evaluate the retention of the amount of exchangeable anions after the interface layer was formed.
[0026] Furthermore, the Zr / P atomic ratio of the zirconium phosphate selective interface layer was determined using the dried composite film as the test sample. X-ray photoelectron spectroscopy was used to detect the Zr3d and P2p signals on the surface of the zirconium phosphate selective interface layer, and the corresponding peak areas were recorded. After correction according to the instrument's relative sensitivity factor, the atomic ratio of zirconium atoms to phosphorus atoms was calculated. The obtained Zr / P atomic ratio was used to characterize the relative composition of zirconium and phosphorus elements in the zirconium phosphate selective interface layer.
[0027] Furthermore, the thickness of the zirconium phosphate selective interface layer was measured using the cross-section of the dried composite film as the test sample. Cross-sectional images were acquired using a scanning electron microscope or a transmission electron microscope. At least three locations were selected on the same film cross-section to measure the local thickness of the zirconium phosphate selective interface layer, and the arithmetic mean of the thicknesses at each measurement location was taken as the thickness of the zirconium phosphate selective interface layer.
[0028] Furthermore, the residual N-methylpyrrolidone was detected using the porous support layer after phase inversion, washing, and drying as the test sample. The test sample was weighed and then solvent extracted. The N-methylpyrrolidone content in the extract was determined by gas chromatography. The mass of the test sample, the volume of the extract, and the chromatographic peak area were recorded. The mass fraction of N-methylpyrrolidone in the porous support layer was calculated based on the mass of the test sample. The obtained mass fraction was used to determine whether the residual N-methylpyrrolidone was not greater than 0.5 wt%.
[0029] Furthermore, the moisture content of the anion exchange active layer was detected using membrane samples that had undergone trimethylamine quaternization, washing, and drying. The wet weight of the sample after water absorption equilibrium and the dry weight after re-drying were weighed. The moisture content was calculated by subtracting the dry weight from the wet weight, dividing by the wet weight, and then multiplying by 100%. The resulting moisture content was used to characterize the water content of the anion exchange active layer.
[0030] Furthermore, in the diffusion dialysis performance test, iron-containing nitric acid waste liquid was used as the feed liquid, and deionized water or an aqueous solution of nitric acid with an initial nitric acid mass fraction of 0.1-5.0 wt% was used as the receiving liquid. The diffusion dialysis unit was operated under the conditions of 20-45℃, a feed liquid to receiving liquid volumetric flow rate ratio of 1:0.8 to 1:1.2, and a transmembrane pressure difference of no more than 0.05 MPa. Samples were collected from the feed liquid, receiving liquid, recovered acid solution, and iron-enriched solution. The free nitric acid mass fraction and total iron concentration (calculated as Fe) in each liquid were measured, and the acid recovery amount and iron migration amount were calculated based on the test results. The volumetric flow rate ratio is the ratio of the volumetric flow rate on the feed liquid side to the volumetric flow rate on the receiving liquid side of the diffusion dialysis unit. When free nitric acid is expressed as a mass fraction, it is converted to nitric acid mass according to liquid density and volume; when the total iron concentration is expressed as g / L, it is converted to iron mass according to liquid volume. The nitric acid recovery rate Racid is calculated as "Racid = (mass of newly added nitric acid on the receiving side / initial nitric acid mass in the feed liquid) × 100%", and the iron migration rate Re is calculated as "RFe = (mass of newly added iron on the receiving side / initial total iron mass in the feed liquid) × 100%". The acid-iron separation factor β is calculated as "β = Jacid / JFe", where Jacid is the nitric acid migration normalized to the effective membrane area and operating time, and JFe is the iron migration in Fe form normalized to the effective membrane area and operating time. Each test group uses n ≥ 3 parallel samples, and the values are recorded as mean ± standard deviation.
[0031] Furthermore, free nitric acid was determined using an acid-base titration method corrected for an iron salt blank. When determining the iron concentration in the sample, an iron salt blank system corresponding to the total iron concentration of the sample but without free nitric acid was prepared. Titration was performed at the same dilution factor and endpoint, and the consumption of the blank system was deducted from the consumption of the sample titration. The total iron concentration was determined using inductively coupled plasma atomic emission spectrometry (ICP-AES) or atomic absorption spectrometry, and the sample dilution factor, calibration curve, detection signal, and calculation results were recorded.
[0032] Furthermore, during online flushing, deionized water or a nitric acid aqueous solution with a mass fraction of 0.1-5.0 wt% is allowed to flow through the feed liquid side and the receiving liquid side of the diffusion dialysis unit. The online flushing time is 0.2-2 hours. After the online flushing is completed, the flushing liquid is discharged, and then the iron-containing nitric acid waste liquid and the receiving liquid are reintroduced into the diffusion dialysis unit for diffusion dialysis operation.
[0033] As another concept of this invention, the present invention employs a diffusion dialysis recovery preparation and operation design using an assembled asymmetric composite anion exchange membrane, primarily for achieving, fixing, or amplifying the aforementioned synergistic effects. While increasing the density of the support structure of existing diffusion dialysis membranes generally benefits membrane integrity and pressure resistance, it weakens acid migration capacity due to limited mass transfer channels. Constructing an ultrathin selective layer alone may improve interfacial selectivity but reduce erosion resistance and long-term stability. This invention utilizes a porous polyvinylidene fluoride support layer to support membrane strength, a cross-linked quaternized aromatic polymer layer to provide anion exchange channels, and an in-situ zirconium phosphate selective interface layer on the outer surface, spatially layering the support, exchange, and selection functions. Simultaneously, temperature, flow ratio, and pressure differential control reduce the risk of iron ion migration and membrane fouling, creating a synergistic process system for acid recovery, iron enrichment, and continuous operation and maintenance.
[0034] The porous polyvinylidene fluoride (PVDF) support layer primarily addresses membrane strength, dimensional stability, and liquid channel retention. However, an overly dense support structure can increase resistance to transmembrane migration of acid and hydrogen ions, reducing recovery efficiency. The zirconium phosphate selective interface layer mainly improves interfacial selectivity in iron-containing nitric acid systems and addresses the issue of iron ions entering the recovered acid solution. However, if this interface were to solely handle membrane stability, it would be susceptible to variations in thickness, adhesion status, and operational erosion. A cross-linked quaternized aromatic polymer layer lies between the two, providing exchangeable anion sites and buffering the functional differences between the inorganic interface and the organic support. This invention, through the hierarchical configuration and membrane orientation control of the porous support layer, cross-linked quaternized aromatic polymer layer, and zirconium phosphate selective interface layer, achieves mutual correction between structural support, ion migration, and interfacial sieving, ultimately balancing membrane structural stability and selective separation capability.
[0035] Beneficial technical effects 1. This invention uses a porous polyvinylidene fluoride support layer as the membrane base. By controlling the pore size and thickness, it provides a stable liquid channel for diffusion dialysis, while avoiding the increase in mass transfer resistance caused by simple densification support. This allows the membrane to maintain good structural integrity and acid migration adaptability in the operating environment of iron-containing nitric acid waste liquid.
[0036] 2. In this invention, a cross-linked quaternized aromatic polymer layer is constructed on one side of the porous support layer. Exchangeable anion sites are formed by in-situ polymerization of 4-vinylbenzyl chloride and divinylbenzene and quaternization of trimethylamine. This enables the active layer to have both process controllability and ion exchange capability, reducing the risk of narrowing the process window caused by simply increasing the fixed charge density.
[0037] 3. In this invention, a zirconium phosphate selective interface layer is formed in situ on the outer surface of the anion exchange active layer, so that the iron-containing nitric acid waste liquid on the feed side first contacts the inorganic selective interface and then enters the organic ion exchange layer. This helps to reduce the degree of iron ions entering the recovered acid liquid and enables the two objectives of acid recovery and iron enrichment to be achieved synergistically in the same membrane structure.
[0038] 4. This invention combines diffusion dialysis operating conditions, solid-liquid separation, countercurrent operation, online flushing, and subsequent treatment of iron-rich solution, so that the recovered acid can be returned to the acid preparation process, and the iron-rich solution can be further evaporated and concentrated or hydrolyzed. Compared with the traditional neutralization treatment path, this is more conducive to reducing reagent consumption and salt-containing residual liquid burden. Attached Figure Description
[0039] Figure 1 The graph shows the effect of zirconium phosphate selective interface layer thickness on nitric acid recovery and iron-acid separation factor, based on the membrane material system of Example 1.
[0040] Figure 2 The graph shows the effect of the thickness of the anion exchange active layer on the nitric acid recovery rate and the ferric acid separation factor, based on the membrane material system of Example 1.
[0041] Figure 3 The graph shows the effect of ion exchange capacity on nitric acid recovery and iron-acid separation factor, based on the membrane material system of Example 1.
[0042] Figure 4 The graph shows the effect of the receiving liquid / feed liquid volumetric flow rate ratio on nitric acid recovery and ferric acid separation factor, based on the membrane material system of Example 1.
[0043] Figure 5 The following is a statistical chart of the thickness of the porous support layer in Example 1, Comparative Example 9, and Comparative Example 10.
[0044] Figure 6 The graph shows the thickness of the anion exchange active layer in Examples 1, 9, and 10.
[0045] Figure 7 The graph shows the thickness of the zirconium phosphate selective interface layer in Examples 1, 6, and 9.
[0046] Figure 8 The graphs show the differential pore size distribution of the porous support layer in Examples 1, 1, and 2.
[0047] Figure 9 The cumulative pore size distribution curves of the porous support layer in Example 1, Comparative Example 1, and Comparative Example 2 are shown.
[0048] Figure 10 The porosity statistics of the porous support layer in Example 1, Comparative Example 1, and Comparative Example 2 are shown in the figure.
[0049] Figure 11 The chart shows the ion exchange capacity statistics for Example 1, Comparative Example 5, Comparative Example 9, and Comparative Example 10.
[0050] Figure 12 The graph shows the water content of the membrane samples from Example 1, Comparative Example 5, Comparative Example 9, and Comparative Example 10.
[0051] Figure 13 The graphs show the rate of change of film thickness during continuous operation for Examples 1, 3, and 4.
[0052] Figure 14 The XPS Zr3d high-resolution spectra are for Example 1, Comparative Example 6, and Comparative Example 9.
[0053] Figure 15 The XPS P2p high-resolution spectra of Example 1, Comparative Example 6, and Comparative Example 9 are shown.
[0054] Figure 16 The graph shows the Zr / P atomic ratio on the film surface of Examples 1, 6, and 9.
[0055] Figure 17 The graphs show the time curves of nitric acid recovery rate during diffusion dialysis for Examples 1, 9, and 11.
[0056] Figure 18 The graph shows the total iron concentration over time in the recovered acid solution of Examples 1, 9, and 11.
[0057] Figure 19 The time curves of the acid-iron separation factor are shown for Example 1, Comparative Example 9, and Comparative Example 11.
[0058] Figure 20 The images show a comparison of macroscopic optical photographs of the final product of Example 1 and the final product of Comparative Example 10; where a is a macroscopic optical photograph of the final product of Example 1 and b is a macroscopic optical photograph of the final product of Comparative Example 10.
[0059] Figure 21 The images show a comparison of the scanning electron microscope (SEM) morphology of the final product of Example 1 and the final product of Comparative Example 10; where a is a low-magnification SEM image of the final product of Example 1; b is a low-magnification SEM image of the final product of Comparative Example 10; c is a medium-magnification SEM image of the final product of Example 1; d is a medium-magnification SEM image of the final product of Comparative Example 10; e is a high-magnification SEM image of the final product of Example 1; and f is a high-magnification SEM image of the final product of Comparative Example 10.
[0060] Figure 22The images show a comparison of the transmission electron microscope (TEM) structures of the final product of Example 1 and the final product of Comparative Example 10; where a is a bright-field TEM image of the final product of Example 1; b is a bright-field TEM image of the final product of Comparative Example 10; c is a high-resolution TEM image of the final product of Example 1; d is a high-resolution TEM image of the final product of Comparative Example 10; e is an elemental distribution map of the final product of Example 1; and f is an elemental distribution map of the final product of Comparative Example 10. Detailed Implementation
[0061] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0062] Example 1 S1: Preparation target and feed liquid state In this embodiment, an asymmetric composite anion exchange membrane with an effective membrane area of 100 cm² was prepared and installed in a small plate-and-frame diffusion dialysis unit. The feed solution was iron-containing nitric acid waste liquid from a metal chemical polishing process, with a free nitric acid mass fraction of 3.0 wt% and a total iron concentration (calculated as Fe) of 10 g / L. 3+ The concentration, calculated as Fe, is 7 g / L. 2+ The concentration, calculated as Fe, is 3 g / L. Before entering the diffusion dialysis unit, the feed liquid undergoes solid-liquid separation using a 1 μm pore size filter material, resulting in a suspended solids content of 0.20 wt% after filtration. The receiving liquid is an aqueous solution of nitric acid with an initial nitric acid mass fraction of 0.1 wt%.
[0063] S2: Preparation of porous support layer 15 parts by mass of polyvinylidene fluoride (PVDF) were added to 85 parts by mass of N-methylpyrrolidone (N-Methylpyrrolidone). PVDF was a commercially available chemically pure resin with a moisture content ≤0.10 wt%, and N-methylpyrrolidone was a commercially available analytically pure solvent. The mixture was mechanically stirred at 300 rpm for 4 hours at 50°C to obtain a uniform casting solution free of visible particles. The casting solution was coated onto a clean glass plate to a wet film thickness of 100 μm. After standing in air at 15°C for 10 seconds, the plate was immersed in deionized water at 5°C for 10 minutes for phase inversion. The plate was then washed with deionized water until the residual N-methylpyrrolidone content in the membrane was no more than 0.5 wt%, and then dried in a forced-air environment at 40°C for 2 hours to obtain a porous support layer.
[0064] S3: Preparation of Anion Exchange Active Layer Using the porous support layer of this embodiment as a substrate, a precursor solution was prepared by mixing 10 parts by mass of 4-vinylbenzyl chloride, 0.5 parts by mass of divinylbenzene, 0.1 parts by mass of 2,2'-azobisisobutyronitrile, and 20 parts by mass of N-methylpyrrolidone. 4-Vinylbenzyl chloride, divinylbenzene, and 2,2'-azobisisobutyronitrile were all commercially available chemically pure reagents. The precursor solution was uniformly coated onto one side of the porous support layer and reacted at 60°C for 1 hour under nitrogen protection (nitrogen purity ≥ 99.9%), with the system pressure at atmospheric pressure. After the reaction, the mixture was washed once with N-methylpyrrolidone and once with deionized water, and then dried at 40°C for 2 hours to obtain the crosslinked chloromethyl precursor layer. Based on the dry weight before and after drying, the mass increase of the crosslinked chloromethyl precursor layer relative to the porous support layer was 5%.
[0065] S4: Quaternization and Zirconium Phosphate Selective Interface Layer Formation The cross-linked chloromethyl precursor layer was placed in a sealed container, and the membrane was completely immersed in a 20 wt% trimethylamine aqueous solution. The reaction was carried out at 20 °C for 2 h. After the reaction, the membrane was removed, washed with deionized water until the pH of the washing solution on the membrane surface reached 6, and then dried at 30 °C for 1 h to obtain the anion exchange active layer. Then, the outer surface of the anion exchange active layer was contacted with a 0.02 mol / L zirconium oxychloride octahydrate aqueous solution on one side for 1 min, and then contacted with a 0.05 mol / L phosphoric acid aqueous solution on one side for 5 min. After washing with deionized water, the membrane was dried at 25 °C for 0.5 h to obtain the zirconium phosphate selective interface layer.
[0066] S5: Diffusion Dialysis Operation and Quality Testing When installing the membrane, the zirconium phosphate selective interface layer should face the feed liquid side, and the porous support layer should face the receiver liquid side. The feed liquid and receiver liquid pass through the diffusion dialysis unit in a countercurrent manner, with a linear velocity of 0.03 m / s on both sides, an operating temperature of 20℃, a feed liquid to receiver liquid volumetric flow rate ratio of 1:0.8, and a transmembrane pressure difference of 0.05 MPa. After continuous operation for 8 hours, the membrane is flushed online with 0.1 wt% nitric acid aqueous solution for 0.2 hours. The test results were as follows: the porous support layer had an average pore size of 20 nm, a thickness of 45 μm, a porosity of 40 vol%, and a residual N-methylpyrrolidone content of 0.50 wt%; the anion exchange active layer had a thickness of 0.3 μm, a water content of 10 wt%, and an ion exchange capacity of 0.8 mmol / g; the zirconium phosphate selective interface layer had a loading of 0.05 mg / cm², a thickness of 20 nm, and a Zr / P atomic ratio of 0.6; the free nitric acid mass fraction in the recovered acid solution was 5.0 wt%, and the total iron concentration (calculated as Fe) was 1.5 g / L. Three parallel samples were taken for each test, and the results were recorded as the average value.
[0067] Features and application scenarios of this embodiment This embodiment employs a membrane structure and mild operating conditions geared towards low-value regions, making it suitable for treating metal chemical polishing wastewater with low acidity, low iron content, and finely filtered suspended solids. The membrane structure is characterized by a thin active layer and a thin zirconium phosphate selective interface layer, facilitating the feasibility of acid recovery and low-energy consumption in small-scale diffusion dialysis operations.
[0068] Example 2 Raw materials and proportions This embodiment prepares an asymmetric composite anion exchange membrane with an effective membrane area of 100 cm². The porous support layer uses 25 parts by weight of commercially available chemically pure polyvinylidene fluoride and 75 parts by weight of commercially available analytically pure N-methylpyrrolidone. The crosslinked chloromethyl precursor layer uses 40 parts by weight of 4-vinylbenzyl chloride, 8 parts by weight of divinylbenzene, 2 parts by weight of 2,2'-azobisisobutyronitrile, and 60 parts by weight of N-methylpyrrolidone. The quaternizing agent is a 35 wt% aqueous solution of trimethylamine. The zirconium phosphate selective interface layer uses a 0.20 mol / L aqueous solution of zirconium oxychloride octahydrate and a 0.50 mol / L aqueous solution of phosphoric acid.
[0069] Preparation process Polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (N-Methylpyrrolidone) were added to a solvent-resistant container equipped with a mechanical stirrer and stirred at 500 rpm for 10 h at 70 °C to obtain a uniform casting solution free of visible particles. The casting solution was then coated into a film with a wet film thickness of 250 μm. After standing at 35 °C for 120 s, the film was immersed in deionized water at 25 °C for a phase inversion of 30 min. The phase-inverted film was continuously washed with deionized water until the residual N-methylpyrrolidone content in the film was no more than 0.5 wt%, and then dried at 70 °C for 10 h to obtain a porous support layer.
[0070] Post-processing After coating one side of the porous support layer with the precursor solution, the reaction was carried out at 80°C for 4 hours under nitrogen protection. After the reaction, the membrane was washed three times sequentially with N-methylpyrrolidone and deionized water, and then dried at 60°C for 4 hours to obtain a cross-linked chloromethyl precursor layer with a mass increase of 25%. The membrane was then completely immersed in a 35wt% trimethylamine aqueous solution and reacted at 40°C for 12 hours. It was then washed with deionized water until the pH of the washing solution reached 8, and dried at 60°C for 6 hours to form the anion exchange active layer. Subsequently, the outer surface of the anion exchange active layer was sequentially contacted with a 0.20 mol / L zirconium oxychloride octahydrate aqueous solution for 15 minutes and then with a 0.50 mol / L phosphoric acid aqueous solution for 60 minutes on one side. After washing with deionized water, the membrane was dried at 50°C for 4 hours to obtain the composite membrane.
[0071] Quality inspection or performance testing In this embodiment, the porous support layer has an average pore size of 150 nm, a thickness of 170 μm, a porosity of 75 vol%, and a residual N-methylpyrrolidone content of 0.30 wt%. The anion exchange active layer has a thickness of 1.5 μm, a water content of 45 wt%, and an ion exchange capacity of 1.8 mmol / g. The zirconium phosphate selective interface layer has a loading of 0.50 mg / cm², a thickness of 120 nm, and a Zr / P atomic ratio of 1.4. The membrane is installed in the diffusion dialysis unit, with the zirconium phosphate selective interface layer facing the feed liquid side and the porous support layer facing the receiving liquid side. The feed liquid is iron-containing nitric acid waste liquid from the stainless steel pickling process, with a free nitric acid mass fraction of 25.0 wt% and a total iron concentration (Fe) of 150 g / L. 3+ The concentration, calculated as Fe, is 110 g / L. 2+ The iron concentration (calculated as Fe) was 40 g / L. The feed solution underwent solid-liquid separation using a 50 μm filter material, resulting in a suspended solids content of 0.90 wt%. The receiving solution was a 5.0 wt% nitric acid aqueous solution. The operating temperature was 45℃, the feed-to-receiver volumetric flow rate ratio was 1:1.2, the transmembrane pressure difference was 0.05 MPa, and the linear velocities on both sides were 0.12 m / s. After 72 hours of continuous operation, the solution was flushed online for 2 hours with a 5.0 wt% nitric acid aqueous solution. The recovered acid solution contained 20.0 wt% free nitric acid and a total iron concentration (calculated as Fe) of 8.0 g / L. The iron-enriched solution was concentrated by evaporation and used to prepare iron resource products. Three parallel samples were taken for each test, and the results were recorded as the average value.
[0072] Features of the solution in this embodiment This embodiment employs a membrane preparation scheme with high-value ratio parameters, coupled with feed conditions of high acidity and high iron content, making it suitable for treating stainless steel pickling wastewater with both high acid concentration and high iron load. The membrane structure features a thick support layer, high ion exchange capacity, and a thick zirconium phosphate selective interface layer, demonstrating structural load-bearing capacity and selective separation adaptability under high-load operation.
[0073] Example 3 This embodiment employs a medium-scale preparation method to fabricate an asymmetric composite anion exchange membrane with an effective membrane area of 150 cm², which is then used for the treatment of iron-containing nitric acid wastewater from a metal etching process. The feed solution contains 14.0 wt% free nitric acid and a total iron concentration (calculated as Fe) of 80 g / L. 3+ The concentration, calculated as Fe, is 55 g / L. 2+ The concentration, calculated as Fe, is 25 g / L. Before entering the diffusion dialysis unit, the feed liquid undergoes solid-liquid separation using 10 μm filter material, resulting in a suspended solids content of 0.50 wt%. The receiving liquid is a 0.1 wt% nitric acid aqueous solution.
[0074] The porous support layer in this embodiment was prepared using 20 parts by mass of polyvinylidene fluoride (PVDF) and 80 parts by mass of N-methylpyrrolidone (N-Methylpyrrolidone). PVDF was added to N-Methylpyrrolidone and stirred at 400 rpm for 7 hours at 60°C to obtain a uniform casting solution free of visible particles. The casting solution was coated to a wet film thickness of 180 μm, allowed to stand at 25°C for 60 seconds, and then immersed in deionized water at 15°C for a phase inversion of 20 minutes. After the phase inversion was complete, the film was washed with deionized water until the residual N-methylpyrrolidone content in the film was 0.20 wt%, and then dried at 55°C for 6 hours to obtain the porous support layer.
[0075] A precursor solution consisting of 25 parts by mass of 4-vinylbenzyl chloride, 4 parts by mass of divinylbenzene, 1 part by mass of 2,2'-azobisisobutyronitrile, and 40 parts by mass of N-methylpyrrolidone was coated on one side of the porous support layer. The coated membrane was reacted at 70°C for 2.5 h under nitrogen protection to allow the 4-vinylbenzyl chloride and divinylbenzene to polymerize in situ. After the reaction, the membrane was washed twice sequentially with N-methylpyrrolidone and deionized water, and then dried at 50°C for 3 h to obtain a crosslinked chloromethyl precursor layer with a mass increment of 14%.
[0076] The cross-linked chloromethyl precursor layer was completely immersed in a 28 wt% trimethylamine aqueous solution and reacted at 30 °C for 6 h. After the reaction, the membrane was washed with deionized water until the pH of the washing solution reached 7, and then dried at 45 °C for 3 h to obtain the anion exchange active layer. Subsequently, the outer surface of the anion exchange active layer was contacted on one side with a 0.10 mol / L zirconium oxychloride octahydrate aqueous solution for 8 min, and then on one side with a 0.25 mol / L phosphoric acid aqueous solution for 30 min. After washing with deionized water, the membrane was dried at 35 °C for 2 h to obtain the zirconium phosphate selective interface layer.
[0077] The resulting composite membrane has a porous support layer with an average pore size of 90 nm, a thickness of 100 μm, and a porosity of 58 vol%; an anion exchange active layer with a thickness of 0.9 μm, a water content of 28 wt%, and an ion exchange capacity of 1.2 mmol / g; and a zirconium phosphate selective interface layer with a loading of 0.25 mg / cm², a thickness of 70 nm, and a Zr / P atomic ratio of 1.0. The membrane was installed in a diffusion dialysis unit, with the feed and receiver solutions flowing countercurrently. The operating temperature was 32 °C, the feed to receiver flow rate ratio was 1:1.0, the transmembrane pressure difference was 0.03 MPa, and the linear velocities on both sides were 0.07 m / s. After 24 hours of continuous operation, the membrane was rinsed online with deionized water for 1 hour. The recovered acid solution contained 12.0 wt% free nitric acid and 3.0 g / L total iron (Fe). The iron-enriched solution was used to prepare iron resource products after hot hydrolysis. Three parallel samples were taken for each test, and the results were recorded as the average value.
[0078] The process features and application directions of this embodiment This embodiment employs intermediate-range proportions and operating conditions, balancing membrane preparation controllability, acid migration capacity, and iron retention capacity. It is suitable for continuous treatment of metal etching wastewater with moderate acidity and iron content. In this embodiment, the zirconium phosphate selective interface layer thickness, Zr / P atomic ratio, and water content are all within the intermediate range, facilitating the demonstration of the composite membrane's stable operation within the conventional process window.
[0079] Example 4 I. Sample Size and Waste Liquid Composition: An asymmetric composite anion exchange membrane with an effective membrane area of 200 cm² was used as the treatment unit. The feed liquid was iron-containing nitric acid waste liquid generated from the wet leaching process, with a free nitric acid mass fraction of 3.0 wt% and a total iron concentration (calculated as Fe) of 150 g / L. 3+ The concentration, calculated as Fe, is 100 g / L. 2+ The concentration, calculated as Fe, was 50 g / L. The feed liquid underwent solid-liquid separation using 50 μm filter media, resulting in a suspended solids content of 0.98 wt% after filtration. The receiving liquid was a 5.0 wt% nitric acid aqueous solution.
[0080] II. Preparation of Porous Support Layer: 18 parts by weight of polyvinylidene fluoride (PVDF) were added to 82 parts by weight of N-methylpyrrolidone (N-methylpyrrolidone), and stirred at 450 rpm for 10 h at 70 °C to obtain a uniform casting solution free of visible particles. The casting solution was coated into a film with a wet film thickness of 250 μm, and after standing at 35 °C for 120 s, it was immersed in deionized water at 25 °C for 30 min for phase inversion. The phase-inverted film was washed with deionized water until the residual N-methylpyrrolidone content in the film was no more than 0.5 wt%, and then dried at 70 °C for 10 h to obtain a porous support layer. The test results showed that the average pore size of the porous support layer in this embodiment was 145 nm, the thickness was 168 μm, the porosity was 72 vol%, and the residual N-methylpyrrolidone content was 0.40 wt%.
[0081] III. Preparation of the Active Layer: Using a porous support layer as a substrate, a precursor solution was prepared by mixing 32 parts by mass of 4-vinylbenzyl chloride, 6 parts by mass of divinylbenzene, 1.5 parts by mass of 2,2'-azobisisobutyronitrile, and 50 parts by mass of N-methylpyrrolidone, and coated onto one side of the porous support layer. Under nitrogen protection, the reaction was carried out at 80°C for 4 hours to allow in-situ polymerization of 4-vinylbenzyl chloride and divinylbenzene. After the reaction, the membrane was washed three times sequentially with N-methylpyrrolidone and deionized water to obtain a cross-linked chloromethyl precursor layer with a mass increase of 22%. This precursor layer was completely immersed in a 35wt% trimethylamine aqueous solution and reacted at 40°C for 12 hours. The membrane was washed until the pH of the washing solution reached 8, and then dried at 60°C for 6 hours to obtain the anion exchange active layer. The results showed that the anion exchange active layer had a water content of 42wt%, an ion exchange capacity of 1.7 mmol / g, and a thickness of 1.4 μm.
[0082] IV. Interfacial Layer Formation and Operation: The outer surface of the anion exchange active layer was contacted with a 0.20 mol / L zirconium oxychloride octahydrate aqueous solution on one side for 15 min, and then contacted with a 0.50 mol / L phosphoric acid aqueous solution on one side for 60 min. The mixture was washed with deionized water and dried at 50℃ for 4 h to obtain the zirconium phosphate selective interfacial layer. The test results showed that the zirconium phosphate selective interfacial layer had a loading of 0.48 mg / cm², a thickness of 118 nm, and a Zr / P atomic ratio of 1.3. During diffusion dialysis operation, the zirconium phosphate selective interfacial layer faced the feed liquid side, and the porous support layer faced the receiver liquid side. The feed liquid and receiver liquid flowed countercurrently through the diffusion dialysis unit, with a linear velocity of 0.12 m / s on both sides. The operating temperature was 45℃, the feed liquid to receiver liquid volumetric flow rate ratio was 1:1.2, and the transmembrane pressure difference was 0.04 MPa. After 72 h of continuous operation, the layer was rinsed online with a 5.0 wt% nitric acid aqueous solution for 2 h. The recovered acid solution contained 5.2 wt% free nitric acid and 9.8 g / L total iron (Fe). The iron-enriched solution was further hydrolyzed by hot water and used to prepare iron resource products. Three parallel samples were taken for each test, and the results were recorded as the average value.
[0083] Applicable Scenarios of This Embodiment This embodiment is applicable to wet leaching wastewater treatment scenarios with low acidity and high iron content. The membrane preparation adopts an optimized scheme with a high loading rate, combined with a high flow rate and a long continuous operating time. This scheme helps to demonstrate feasibility over a wide process window, and is particularly suitable for wastewater resource recovery processes with high requirements for iron retention, stable operation, and online flushing recovery.
[0084] Comparative Example 1: Basically the same as Example 1, except that in step S2 the average pore size of the porous support layer was adjusted to 10 nm, the mass fraction of free nitric acid in the feed solution was 3.0 wt%, the total iron concentration (calculated as Fe) was 10 g / L, the receiving solution was a 0.1 wt% nitric acid aqueous solution, the diffusion dialysis temperature was 20 °C, the volume flow ratio of the feed solution to the receiving solution was 1:0.8, the transmembrane pressure difference was 0.05 MPa, the linear velocity on both sides was 0.03 m / s, the thickness of the porous support layer was 45 μm, the thickness of the anion exchange active layer was 0.3 μm, the ion exchange capacity was 0.8 mmol / g, the thickness of the zirconium phosphate selective interface layer was 20 nm, and the Zr / P atomic ratio was 0.6.
[0085] Comparative Example 2: Basically the same as Example 1, except that in step S2 the average pore size of the porous support layer was adjusted to 180 nm, the mass fraction of free nitric acid in the feed solution was 3.0 wt%, the total iron concentration (calculated as Fe) was 10 g / L, the receiving solution was a 0.1 wt% nitric acid aqueous solution, the diffusion dialysis temperature was 20 °C, the volume flow ratio of the feed solution to the receiving solution was 1:0.8, the transmembrane pressure difference was 0.05 MPa, the linear velocity on both sides was 0.03 m / s, the thickness of the porous support layer was 45 μm, the thickness of the anion exchange active layer was 0.3 μm, the ion exchange capacity was 0.8 mmol / g, the thickness of the zirconium phosphate selective interface layer was 20 nm, and the Zr / P atomic ratio was 0.6.
[0086] Comparative Example 3: Basically the same as Example 1, except that in step S4 the thickness of the anion exchange active layer was adjusted to 0.15 μm, the mass fraction of free nitric acid in the feed solution was 3.0 wt%, the total iron concentration (calculated as Fe) was 10 g / L, the receiving solution was a 0.1 wt% nitric acid aqueous solution, the diffusion dialysis temperature was 20 °C, the volume flow ratio of the feed solution to the receiving solution was 1:0.8, the transmembrane pressure difference was 0.05 MPa, the linear velocity on both sides was 0.03 m / s, the average pore size of the porous support layer was 20 nm, the thickness of the porous support layer was 45 μm, the ion exchange capacity was 0.8 mmol / g, the thickness of the zirconium phosphate selective interface layer was 20 nm, and the Zr / P atomic ratio was 0.6.
[0087] Comparative Example 4: Basically the same as Example 1, except that in step S4 the thickness of the anion exchange active layer was adjusted to 2.0 μm, the mass fraction of free nitric acid in the feed solution was 3.0 wt%, the total iron concentration (calculated as Fe) was 10 g / L, the receiving solution was a 0.1 wt% nitric acid aqueous solution, the diffusion dialysis temperature was 20 °C, the volume flow ratio of the feed solution to the receiving solution was 1:0.8, the transmembrane pressure difference was 0.05 MPa, the linear velocity on both sides was 0.03 m / s, the average pore size of the porous support layer was 20 nm, the thickness of the porous support layer was 45 μm, the ion exchange capacity was 0.8 mmol / g, the thickness of the zirconium phosphate selective interface layer was 20 nm, and the Zr / P atomic ratio was 0.6.
[0088] Comparative Example 5: Basically the same as Example 1, except that in step S4 the ion exchange capacity of the anion exchange active layer was adjusted to 0.5 mmol / g, the mass fraction of free nitric acid in the feed solution was 3.0 wt%, the total iron concentration (calculated as Fe) was 10 g / L, the receiving solution was a 0.1 wt% nitric acid aqueous solution, the diffusion dialysis temperature was 20 °C, the volume flow ratio of the feed solution to the receiving solution was 1:0.8, the transmembrane pressure difference was 0.05 MPa, the linear velocity on both sides was 0.03 m / s, the average pore size of the porous support layer was 20 nm, the thickness of the porous support layer was 45 μm, the thickness of the anion exchange active layer was 0.3 μm, the thickness of the zirconium phosphate selective interface layer was 20 nm, and the Zr / P atomic ratio was 0.6.
[0089] Comparative Example 6: Basically the same as Example 1, except that in step S4 the thickness of the zirconium phosphate selective interface layer was adjusted to 10 nm, the mass fraction of free nitric acid in the feed solution was 3.0 wt%, the total iron concentration (calculated as Fe) was 10 g / L, the receiving solution was a 0.1 wt% nitric acid aqueous solution, the diffusion dialysis temperature was 20 °C, the volume flow ratio of the feed solution to the receiving solution was 1:0.8, the transmembrane pressure difference was 0.05 MPa, the linear velocity on both sides was 0.03 m / s, the average pore size of the porous support layer was 20 nm, the thickness of the porous support layer was 45 μm, the thickness of the anion exchange active layer was 0.3 μm, the ion exchange capacity was 0.8 mmol / g, and the Zr / P atomic ratio was 0.6.
[0090] Comparative Example 7: Basically the same as Example 1, except that in step S5 the diffusion dialysis operating temperature was adjusted to 55°C, the feed liquid had a free nitric acid mass fraction of 3.0 wt% and a total iron concentration of 10 g / L (calculated as Fe), the receiving liquid was a 0.1 wt% nitric acid aqueous solution, the feed liquid to receiving liquid volume flow ratio was 1:0.8, the transmembrane pressure difference was 0.05 MPa, the linear velocity on both sides was 0.03 m / s, the average pore size of the porous support layer was 20 nm, the thickness of the porous support layer was 45 μm, the thickness of the anion exchange active layer was 0.3 μm, the ion exchange capacity was 0.8 mmol / g, the thickness of the zirconium phosphate selective interface layer was 20 nm, and the Zr / P atomic ratio was 0.6.
[0091] Comparative Example 8: Basically the same as Example 1, except that in step S5 the volume flow ratio of feed liquid to receiving liquid is adjusted to 1:1.5, the mass fraction of free nitric acid in the feed liquid is 3.0 wt%, the total iron concentration (calculated as Fe) is 10 g / L, the receiving liquid is a 0.1 wt% nitric acid aqueous solution, the diffusion dialysis temperature is 20 °C, the transmembrane pressure difference is 0.05 MPa, the linear velocity on both sides is 0.03 m / s, the average pore size of the porous support layer is 20 nm, the thickness of the porous support layer is 45 μm, the thickness of the anion exchange active layer is 0.3 μm, the ion exchange capacity is 0.8 mmol / g, the thickness of the zirconium phosphate selective interface layer is 20 nm, and the Zr / P atomic ratio is 0.6.
[0092] Comparative Example 9: Essentially the same as Example 1, except that a zirconium phosphate selective interface layer is not formed in step S4. The membrane consists of a porous polyvinylidene fluoride support layer and a cross-linked quaternized aromatic polymer layer. The feed solution has a free nitric acid mass fraction of 3.0 wt% and a total iron concentration (calculated as Fe) of 10 g / L. The receiving solution is a 0.1 wt% nitric acid aqueous solution. The diffusion dialysis temperature is 20 °C. The feed-to-receiver volumetric flow rate ratio is 1:0.8. The transmembrane pressure difference is 0.05 MPa, the linear velocity across the membrane is 0.03 m / s, the average pore size of the porous support layer is 20 nm, the thickness of the porous support layer is 45 μm, the thickness of the anion exchange active layer is 0.3 μm, and the ion exchange capacity is 0.8 mmol / g. This comparative example is used to investigate the synergistic relationship between the cross-linked quaternized aromatic polymer layer and the zirconium phosphate selective interface layer.
[0093] Comparative Example 10: Essentially the same as Example 1, except that in steps S3 and S4, no cross-linked quaternized aromatic polymer layer is formed. Instead, a porous polyvinylidene fluoride support layer is sequentially contacted with a 0.02 mol / L zirconium oxychloride octahydrate aqueous solution and a 0.05 mol / L phosphoric acid aqueous solution to form a zirconium phosphate treated layer. The feed solution has a free nitric acid mass fraction of 3.0 wt% and a total iron concentration (calculated as Fe) of 10 g / L. The receiving solution is a 0.1 wt% nitric acid aqueous solution. The diffusion dialysis temperature is 20°C. The feed-to-receiver volumetric flow rate ratio is 1:0.8. The transmembrane pressure difference is 0.05 MPa. The linear velocities on both sides are 0.03 m / s. The average pore size of the porous support layer is 20 nm, the thickness of the porous support layer is 45 μm, the thickness of the zirconium phosphate treated layer is 20 nm, and the Zr / P atomic ratio is 0.6. This comparative example is used to investigate the hierarchical synergistic relationship between the porous polyvinylidene fluoride support layer, the cross-linked quaternized aromatic polymer layer, and the zirconium phosphate selective interface layer.
[0094] Comparative Example 11: This example is essentially the same as Example 1, except that in step S5, when installing the membrane, the porous support layer faces the feed liquid side, and the zirconium phosphate selective interface layer faces the receiver liquid side. The feed liquid has a free nitric acid mass fraction of 3.0 wt% and a total iron concentration (calculated as Fe) of 10 g / L. The receiver liquid is a 0.1 wt% nitric acid aqueous solution. The diffusion dialysis temperature is 20°C, the feed liquid to receiver liquid volumetric flow rate ratio is 1:0.8, the transmembrane pressure difference is 0.05 MPa, the linear velocity on both sides is 0.03 m / s, the average pore size of the porous support layer is 20 nm, the thickness of the porous support layer is 45 μm, the thickness of the anion exchange active layer is 0.3 μm, the ion exchange capacity is 0.8 mmol / g, the thickness of the zirconium phosphate selective interface layer is 20 nm, and the Zr / P atomic ratio is 0.6. This comparative example is used to investigate the synergistic relationship between membrane orientation and hierarchical structure.
[0095] Characterization tests: The performance of diffusion dialysis separation was evaluated using the recovered acid solution and iron-rich solution from Examples 1–4 and all comparative examples. The principle is that free nitric acid migrates to the receiving liquid side via the anion exchange membrane, while iron ions are mainly retained on the feed liquid side. Free nitric acid was determined by acid-base titration with iron salt blank correction, and total iron concentration was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) or atomic absorption spectrometry. The volumes of feed liquid, receiving liquid, recovered acid solution, and iron-rich solution were recorded. For each group, n≥3, the nitric acid recovery rate, iron migration rate, and acid-iron separation factor were calculated.
[0096] Nitric acid recovery rate was calculated as the percentage of newly added nitric acid mass on the receiving side relative to the initial nitric acid mass in the feed liquid; iron migration rate was calculated as the percentage of newly added iron mass on the receiving side relative to the initial total iron mass in the feed liquid; the acid-iron separation factor was calculated as the ratio of nitric acid migration flux to iron migration flux (in Fe terms). When calculating the nitric acid mass, the free nitric acid mass fraction was converted to mass based on the corresponding liquid density and volume; when calculating the iron mass, the total iron concentration was converted to mass based on the corresponding liquid volume. Statistical results for each parallel sample were recorded as mean ± standard deviation.
[0097] Using composite membranes before and after operation as test objects, this study evaluates the structural integrity and wet dimensional stability in an acidic iron-containing system. The principle is that acid wetting, iron salt contact, and differential pressure operation may cause changes in membrane thickness, mass loss, or increased differential pressure. A method of constant-temperature immersion, weighing before and after operation, thickness measurement with a membrane thickness gauge, and differential pressure recording were employed. The membranes were treated at 20-45℃ for 8-72 hours, and the membrane mass retention rate, membrane thickness change rate, differential pressure increase rate, and differential pressure recovery rate after rinsing were recorded. The membrane quality retention rate is calculated by dividing the dry membrane mass after operation by the dry membrane mass before operation and then multiplying by 100%; the membrane thickness change rate is calculated by dividing the absolute value of the difference between the average membrane thickness after operation and the average membrane thickness before operation by the average membrane thickness before operation and then multiplying by 100%; the differential pressure growth rate is calculated by dividing the difference between the transmembrane differential pressure after operation and the initial transmembrane differential pressure by the initial transmembrane differential pressure and then multiplying by 100%; the differential pressure recovery rate after flushing is calculated by dividing the difference between the transmembrane differential pressure before flushing and the transmembrane differential pressure after flushing by the difference between the transmembrane differential pressure before flushing and the initial transmembrane differential pressure and then multiplying by 100%.
[0098] The ion exchange capacity and water content were evaluated using a trimethylamine quaternized anion exchange active layer, a composite membrane with a zirconium phosphate selective interface layer, and corresponding proportionate membrane samples. The principle is that the fixed charge of the quaternary ammonium salt determines the anion exchange capacity, while the water content affects ion migration and dimensional stability. The amount of exchangeable anions was determined using the chloride ion exchange capacity method, and the dry membrane mass, exchange solution volume, titrant concentration, and titration volume were recorded. The ion exchange capacity used to characterize the anion exchange active layer was based on the dry membrane of the two-layer composite system with quaternized trimethylamine but without a zirconium phosphate selective interface layer. The water content was calculated by subtracting the dry weight from the wet weight and then dividing by the wet weight.
[0099] Cross-sectional samples containing a porous support layer, an anion exchange active layer, and a zirconium phosphate selective interface layer were used as test objects to evaluate the hierarchical structure dimensions. The principle is that the pore size of the support layer, the thickness of the active layer, and the thickness of the inorganic interface layer collectively affect mass transfer resistance and selectivity. Cross-sectional images were acquired using scanning electron microscopy or transmission electron microscopy. The thicknesses of the porous support layer, the active layer, and the zirconium phosphate selective interface layer were measured at no fewer than three locations on each sample. Pore size was statistically analyzed using cross-sectional or surface images.
[0100] The Zr / P atomic ratio and surface elemental composition were evaluated using the zirconium phosphate selective interface layer surface as the test object. The principle is that after the in-situ reaction of zirconium oxychloride octahydrate with phosphoric acid, the relative ratio of zirconium and phosphorus elements on the interface layer surface reflects the composition of the inorganic selective layer. X-ray photoelectron spectroscopy was used to record the peak areas of Zr3d and P2p signals, and the Zr / P atomic ratio was calculated after correction according to the instrument's relative sensitivity factor.
[0101] Using diffusion dialysis units after continuous operation and online flushing as test objects, the operational retention rate and flushing recoverability were evaluated. The principle is that continuous contact with iron-containing nitric acid waste liquid may cause membrane fouling and pressure differential changes, while online flushing can restore the liquid flow. The units were run for 8 hours, 24 hours, and 72 hours at set times, and the nitric acid recovery rate, total iron concentration in the recovered acid, transmembrane pressure differential, and flow rates before and after flushing were recorded. For each group, n≥3, the acid recovery retention rate, iron leakage change rate, and pressure differential recovery rate were calculated. The acid recovery retention rate was calculated by dividing the nitric acid recovery rate at the end of continuous operation by the nitric acid recovery rate at the initial stable stage and then multiplying by 100%; the iron leakage change rate was calculated by dividing the total iron concentration in the recovered acid at the end of continuous operation by the total iron concentration in the recovered acid at the initial stable stage and then multiplying by 100%.
[0102] Figure 1 The graph shows the effect of zirconium phosphate selective interface layer thickness on nitric acid recovery and iron-acid separation factor, based on the membrane material system of Example 1. Figure 1 The trend test used the same membrane material system and operating method as in Example 1, and tested the samples with independently prepared zirconium phosphate selective interface layer thickness gradients. Figure 1 The data were used to characterize the thickness variation trend, and Table 1 shows the performance data for the examples and comparative examples. The results indicate that when the zirconium phosphate selective interface layer thickness is in the range of approximately 20–120 nm, both the nitric acid recovery rate and the acid-iron separation factor remain at optimal levels. If the interface layer is too thin, its inhibitory effect on iron ion entry into the recovered acid solution is insufficient; if the interface layer is too thick, it increases the resistance to nitric acid migration. This suggests that a zirconium phosphate selective interface layer of moderate thickness can achieve a good balance between acid transport and iron retention.
[0103] Figure 2 The graph shows the effect of the thickness of the anion exchange active layer on the nitric acid recovery rate and the ferric acid separation factor, based on the membrane material system of Example 1. Figure 2The trend test used the same membrane material system and operating method as in Example 1, and tested with independently prepared anion exchange active layer thickness gradient samples. The results showed that when the active layer thickness was approximately 0.30–1.50 μm, the membrane material had both high nitric acid migration capacity and good acid-iron separation capacity; when the active layer was too thin, the continuity and ion exchange sites were insufficient, and when it was too thick, the mass transfer resistance increased. Figure 3 This is a graph showing the effect of ion exchange capacity on nitric acid recovery and ferric acid separation factor, based on the membrane material system of Example 1. Figure 3 The trend test was conducted using independently prepared ion exchange capacity gradient samples. The results showed that the overall performance was better when the ion exchange capacity was about 0.8–1.8 mmol / g, indicating that an appropriate amount of quaternary ammonium groups can provide nitrate migration channels, while avoiding the increase in water content and membrane swelling caused by excessively high ion exchange capacity. Figure 4 This is a graph showing the effect of the receiver / feed volumetric flow rate ratio on nitric acid recovery and ferric acid separation factor, based on the membrane material system of Example 1. Figure 4 This study used the ratio of the receiver liquid-side volumetric flow rate to the feed liquid-side volumetric flow rate to characterize the effect of diffusion dialysis performance. The results showed that when the receiver liquid / feed liquid volumetric flow rate ratio was approximately 0.8–1.2, the system exhibited a reasonable concentration gradient and mass transfer driving force, which was conducive to the migration of nitric acid to the receiver side while inhibiting the accompanying migration of iron ions. This indicates that the proposed scheme has good adaptability to process operating parameters.
[0104] Figure 5 The figures show the thickness statistics of the porous support layer in Examples 1, 9, and 10. Multi-point thickness tests show that the thickness of the polyvinylidene fluoride porous support layer in Example 1 is concentrated around 45 μm, with minimal thickness fluctuation. This indicates that the support layer has good film uniformity and can provide a stable foundation for the subsequent active layer and selective interface layer. Figure 6 The figure shows the thickness of the anion exchange active layer in Example 1, Comparative Example 9, and Comparative Example 10. The results show that Example 1 formed a cross-linked quaternized aromatic polymer anion exchange active layer with a thickness of about 0.30 μm and a continuous distribution, while the active layer in Comparative Example 10 was obviously missing or insufficient. This indicates that Example 1 can effectively construct a functional layer with anion conduction capability. Figure 7 The figures show the thickness of the zirconium phosphate selective interface layer in Examples 1, 6, and 9. The results indicate that Example 1 formed a zirconium phosphate selective interface layer with a thickness of approximately 20 nm, Comparative Example 6 had a relatively thin interface layer, and Comparative Example 9 essentially did not form an effective interface layer. These results, from a thickness control perspective, demonstrate that this method does not rely solely on a support layer or a single inorganic treatment layer to achieve separation, but rather improves overall separation performance through a hierarchical combination of a support layer, an active layer, and a selective interface layer.
[0105] Figure 8The graphs show the differential pore size distribution of the porous support layers in Example 1, Comparative Example 1, and Comparative Example 2. The results show that the pore size distribution in Example 1 is more concentrated, with the main peak located within a moderate nanopore size range. The pore size in Comparative Example 1 is too small, which can easily restrict the diffusion of nitric acid. The pore size in Comparative Example 2 is too large, which may weaken the film support and interface regulation effects. Figure 9 The graphs show the cumulative pore size distribution curves of the porous support layer in Example 1, Comparative Example 1, and Comparative Example 2. The cumulative distribution curve of Example 1 shows a concentrated change, indicating that its pore size uniformity is good, which is beneficial to reducing local mass transfer differences. Figure 10 The figures show the porosity statistics of the porous support layers in Example 1, Comparative Example 1, and Comparative Example 2. The results show that the porosity of Example 1 is approximately 40 vol%, which is different from the situation where low porosity leads to insufficient mass transfer, and also different from the situation where high porosity leads to decreased structural stability. Figures 8 to 10 As can be seen, Example 1, by controlling the pore size distribution and porosity of the support layer, enables the porous support layer to simultaneously play the roles of mechanical support and liquid transport channel, providing a foundation for subsequent acid recovery and continuous operation stability.
[0106] Figure 11 The chart shows the ion exchange capacity of Examples 1, 5, 9 and 10. The results show that the ion exchange capacity of Example 1 is about 0.80 mmol / g, which is within a moderate range that can ensure the migration of anions without excessive water absorption and swelling. The ion exchange capacity of Comparative Example 5 is too low and it is difficult to provide enough nitrate transport sites. Comparative Example 10 has a significantly insufficient ion exchange capacity due to the lack of an effective active layer. Figure 12 The graph shows the water content of the membrane samples from Examples 1, 5, 9 and 10. The results show that the water content of the anion exchange active layer in Example 1 is about 10 wt%, which can form the necessary hydrated ion transport environment while maintaining the stability of the membrane size. Figure 13 The graphs show the membrane thickness change rate curves for Examples 1, 3, and 4 after continuous operation. The results show that Example 1 exhibited a lower membrane thickness change rate after 72 hours of continuous operation, while Comparative Examples 3 and 4 showed more significant thickness changes. Figures 11 to 13 As can be seen, Example 1 controls the ion exchange capacity and water content by crosslinking the quaternized aromatic polymer active layer, avoiding the problem of membrane swelling caused by simply increasing the ion exchange capacity, thus taking into account both the anion migration capacity and the structural stability in the acidic iron-containing system.
[0107] Figure 14 The images show XPS Zr3d high-resolution spectra of Example 1, Comparative Example 6, and Comparative Example 9. The surface of Example 1 shows obvious Zr3d characteristic signals, while the signal in Comparative Example 6 is weaker and the signal in Comparative Example 9 is close to the background level, indicating that zirconium-containing components were introduced into the surface of Example 1. Figure 15The XPS high-resolution spectra of Example 1, Comparative Example 6, and Comparative Example 9 are shown. Example 1 displays a clear P2p characteristic peak, and... Figure 14 The Zr3d signals correspond to each other, indicating the presence of phosphorus-containing components on the membrane surface. Figure 16 The figures show the Zr / P atomic ratios on the film surfaces of Examples 1, 6, and 9. The results show that the Zr / P atomic ratio in Example 1 is approximately 0.60, falling within the Zr / P atomic ratio range defined in this application. Figures 14 to 16 It is known that Zr3d and P2p signals were detected on the membrane surface in Example 1, and the Zr / P atomic ratio fell within the range defined in this application. This result is consistent with the structural description of zirconium-containing phosphate interface components forming on the outside of the anion exchange active layer.
[0108] Figure 17 The graphs show the time curves of nitric acid recovery rate during diffusion dialysis for Examples 1, 9, and 11. The results show that the nitric acid recovery rate of Example 1 steadily increased over time during operation and reached a high level at 8 hours, indicating that its anion exchange active layer can maintain a stable nitric acid migration capacity. Figure 18 The graphs show the total iron concentration over time in the recovered acid solution of Examples 1, 9, and 11. The results show that the total iron concentration in the recovered acid solution of Example 1 is consistently low, while the iron migration in Comparative Examples 9 and 11 is significantly increased. This indicates that when there is a lack of effective selective interfaces or an incomplete hierarchical structure, iron ions are more likely to enter the recovered acid solution. Figure 19 The graphs show the time curves of the acid-iron separation factor for Examples 1, 9, and 11. The results show that Example 1 maintained a high acid-iron separation factor at different operating times. Figures 17 to 19 It can be seen that Example 1 can reduce iron ion migration while ensuring effective recovery of nitric acid, and achieve simultaneous improvement in acid migration efficiency and acid-iron selectivity, directly addressing the problem that acid recovery rate and impurity retention are difficult to balance in the recovery of iron-containing nitric acid waste liquid.
[0109] Figure 20 The image shows a macroscopic optical photograph comparison between the final product of Example 1 and the final product of Comparative Example 10, used to illustrate the overall film-forming effect after the construction of the cross-linked quaternized aromatic polymer anion exchange active layer and the zirconium phosphate selective interface layer. Figure 20 a is a macroscopic optical photograph of the final product of Example 1. The effective membrane area of the sample is 100 cm². It consists of a porous polyvinylidene fluoride support layer with a thickness of about 45 μm and an average pore size of about 20 nm, a cross-linked quaternized aromatic polymer anion exchange active layer with a thickness of about 0.30 μm, and a zirconium phosphate selective interface layer with a thickness of about 20 nm, a loading of about 0.05 mg / cm², and a Zr / P atomic ratio of about 0.60. The membrane is continuous, has a uniform surface, and maintains an intact membrane morphology. Figure 20b is a macroscopic optical photograph of the final product of Comparative Example 10, which consists of a porous polyvinylidene fluoride support layer with a thickness of approximately 45 μm and an average pore size of approximately 20 nm, and a zirconium phosphate treatment layer with a thickness of approximately 20 nm. The cross-linked quaternized aromatic polymer anion exchange active layer with a thickness of approximately 0.30 μm was not formed. Figure 20 Compared to a, Figure 20 b shows that the surface uniformity and hierarchical integrity of the membrane decreased after the organic active layer was missing, indicating that the organic active layer not only provides ion exchange capacity, but also plays a supporting role in the uniform construction of the inorganic selective interface layer.
[0110] Figure 21 The image shows a comparison of the scanning electron microscope morphology of the final product of Example 1 and the final product of Comparative Example 10, which is used to further illustrate the hierarchical structural relationship between the porous support layer, the anion exchange active layer and the zirconium phosphate selective interface layer. Figure 21 a is a low-magnification scanning electron microscope image of the final product of Example 1, showing that the polyvinylidene fluoride porous support layer with a thickness of about 45 μm is continuous as a whole, and no obvious through cracks or delamination are observed in the cross section. Figure 21 b is a low-magnification scanning electron microscope image of the final product of Comparative Example 10, which also has a polyvinylidene fluoride porous support layer with a thickness of about 45 μm and an average pore size of about 20 nm, thus eliminating the influence of the support layer size difference on the comparison results. Figure 21 c is a high-resolution scanning electron microscope image of the final product of Example 1, showing a cross-linked quaternized aromatic polymer anion exchange active layer with a thickness of approximately 0.30 μm covering one side of the porous support layer. Figure 21 Image d is a mid-magnification scanning electron microscope image of the final product of Comparative Example 10, showing that the sample lacks the corresponding organic active layer, and the zirconium phosphate treatment layer is directly located on the surface of the polyvinylidene fluoride porous support layer. Figure 21 e is a high-magnification scanning electron microscope image of the final product of Example 1, showing that a zirconium phosphate selective interface layer with a thickness of about 20 nm is located outside the cross-linked quaternized aromatic polymer anion exchange active layer, and further modulates the interface structure of the surface pore structure of the support layer. Figure 21 f is a high-magnification scanning electron microscope image of the final product of Comparative Example 10, showing that in the absence of an organic active layer, the zirconium phosphate treated layer is in direct contact with the polyvinylidene fluoride surface, resulting in relatively insufficient interfacial continuity and interlayer transition. Figure 21 a to Figure 21 As can be seen from f, the cross-linked quaternized aromatic polymer anion exchange active layer with a thickness of about 0.30 μm is the key structure connecting the porous polyvinylidene fluoride support layer and the zirconium phosphate selective interface layer, which helps to form a stable asymmetric composite membrane cross section.
[0111] Figure 22The image shows a transmission electron microscope comparison of the final product of Example 1 and the final product of Comparative Example 10, used to illustrate the spatial distribution relationship between the organic active layer and the inorganic selective interface layer from a higher resolution scale. Figure 22 Image a is a bright-field transmission electron microscope image of the final product of Example 1, showing that the polyvinylidene fluoride porous support layer, the cross-linked quaternized aromatic polymer anion exchange active layer with a thickness of about 0.30 μm, and the zirconium phosphate selective interface layer with a thickness of about 20 nm are distributed sequentially to form a continuous hierarchical structure. Figure 22 b is a bright-field transmission electron microscope image of the final product of Comparative Example 10, showing that no organic active layer was formed in this sample, and the zirconium phosphate treatment layer was directly adjacent to the polyvinylidene fluoride porous support layer. Figure 22 c is a high-resolution transmission electron microscope image of the final product of Example 1. It can be observed that the zirconium phosphate selective interface layer is located outside the organic active layer. Combined with its thickness of about 20 nm and Zr / P atomic ratio of about 0.60, this result is consistent with the structural description of the distribution of the inorganic selective interface layer on the surface of the active layer. Figure 22 Image d is a high-resolution transmission electron microscope image of the final product of Comparative Example 10, showing that the local interface state of the zirconium phosphate treatment layer is difficult to form an orderly transition when the organic active layer is missing. Figure 22 e is the elemental distribution diagram of the final product of Example 1, where N corresponds to the cross-linked quaternized aromatic polymer anion exchange active layer, and Zr and P correspond to the zirconium phosphate selective interface layer, indicating that the organic active layer and the inorganic selective interface layer have clear spatial partitioning. Figure 22 f is the elemental distribution diagram of the final product of Comparative Example 10, showing that Zr and P elements are directly distributed near the surface of the polyvinylidene fluoride porous support layer. Figure 22 a to Figure 22 As can be seen from f, Example 1 provides mechanical support and liquid channels through a porous polyvinylidene fluoride support layer, provides anion migration capability through a cross-linked quaternized aromatic polymer anion exchange active layer, and reduces the degree of iron ions entering the recovered acid solution through a zirconium phosphate selective interface layer, thereby achieving a synergy of acid migration, iron retention, and continuous operation stability.
[0112] Table 1 Performance summary of examples and comparative examples
[0113] As can be seen from the performance of the examples and comparative examples in Table 1, Examples 1–4 showed a good balance between nitric acid recovery rate, total iron concentration in the recovered acid, acid-iron separation factor, and operational recoverability. In the conventional single-variable comparative examples, smaller pore size, excessively thick active layer, or insufficient ion exchange capacity reduced nitric acid recovery rate, while larger pore size, excessively thin active layer, thin interfacial layer, or higher operating temperature increased the risk of iron entering the recovered acid. In the synergistic comparative examples, the absence of the zirconium phosphate selective interfacial layer, the absence of the cross-linked quaternized aromatic polymer layer, or changes in membrane orientation all resulted in a decrease in the acid-iron separation factor and continuous operation retention rate, indicating that the hierarchical structure and membrane orientation play an important role in balancing membrane structural stability and selective separation capability.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A waste liquid containing iron-containing nitric acid, characterized in that, The iron-containing nitric acid waste liquid is generated from metal pickling, chemical polishing, metal etching, or wet leaching processes. It comprises free nitric acid, dissolved iron ions, and water. The free nitric acid has a mass fraction of 3-25 wt%, and the total iron concentration (calculated as Fe) is 10-150 g / L. The dissolved iron ions are Fe... 3+ and / or Fe 2+ .
2. A method for recycling and reusing iron-containing nitric acid waste liquid as described in claim 1, characterized in that, Includes the following steps: S1. Provide iron-containing nitric acid waste liquid as defined in claim 1 as feed liquid; S2. Use deionized water or an aqueous solution of nitric acid with an initial nitric acid mass fraction of 0.1-5.0 wt% as the receiving liquid; S3. The feed liquid and the receiving liquid are respectively introduced into both sides of the diffusion dialysis unit, and diffusion dialysis is carried out under the conditions of 20-45℃, feed liquid to receiving liquid volume flow ratio of 1:0.8 to 1:1.2, and transmembrane pressure difference not greater than 0.05MPa to obtain recovered acid solution and iron enrichment solution. The diffusion dialysis unit is equipped with an asymmetric composite anion exchange membrane, which includes a porous support layer made of polyvinylidene fluoride, an anion exchange active layer formed on one side of the porous support layer, and a zirconium phosphate selective interface layer formed on the outer surface of the anion exchange active layer. During diffusion dialysis, the zirconium phosphate selective interface layer faces the feed liquid side, and the porous support layer faces the receiving liquid side. The anion exchange active layer is a cross-linked quaternized aromatic polymer layer obtained by polymerizing 4-vinylbenzyl chloride with divinylbenzene and then quaternizing it with trimethylamine. The zirconium phosphate selective interface layer is formed by the in-situ reaction of zirconium oxychloride octahydrate and phosphoric acid on the outer surface of the anion exchange active layer. The porous support layer has an average pore size of 20-150 nm and a thickness of 45-170 μm, the anion exchange active layer has a thickness of 0.3-1.5 μm, and the ion exchange capacity based on the two-layer composite dry membrane system with completed trimethylamine quaternization and no zirconium phosphate selective interface layer is 0.8-1.8 mmol / g, and the zirconium phosphate selective interface layer has a thickness of 20-120 nm. S4. The recovered acid solution is returned to the acid preparation process for reuse, and the iron enrichment solution is used as a raw material for subsequent iron resource utilization treatment.
3. The recycling method according to claim 2, characterized in that, The porous support layer is prepared by the following steps: A1. Based on a total of 100 parts by weight of polyvinylidene fluoride and N-methylpyrrolidone, add 15-25 parts by weight of polyvinylidene fluoride to 75-85 parts by weight of N-methylpyrrolidone, and mechanically stir at 300-500 rpm for 4-10 hours at 50-70°C to obtain a uniform casting solution without visible particles. A2. The casting solution is coated into a film with a wet film thickness of 100-250 μm, and after standing at 15-35℃ for 10-120s, it is immersed in deionized water at 5-25℃ for 10-30min for phase inversion. A3. Wash with deionized water until the residual amount of N-methylpyrrolidone in the membrane formed by phase transformation is no more than 0.5 wt%, and then dry at 40-70°C for 2-10 h to obtain the porous support layer with a porosity of 40-75 vol%.
4. The recycling method according to claim 2, characterized in that, The cross-linked chloromethyl precursor layer of the anion exchange active layer is prepared by the following steps: B1. Using the porous support layer as a substrate, 10-40 parts by weight of 4-vinylbenzyl chloride, 0.5-8 parts by weight of divinylbenzene, 0.1-2 parts by weight of 2,2'-azobisisobutyronitrile and 20-60 parts by weight of N-methylpyrrolidone are formulated into a precursor solution, which is then coated on one side of the porous support layer. B2. Under nitrogen protection, the reaction is carried out at 60-80℃ for 1-4 hours to polymerize the 4-vinylbenzyl chloride and the divinylbenzene in situ. B3. Wash with N-methylpyrrolidone and deionized water 1-3 times in sequence to obtain the crosslinked chloromethyl precursor layer with a mass increment of 5-25% relative to the porous support layer.
5. The recycling method according to claim 4, characterized in that, The anion exchange active layer is prepared by the following steps: C1. The cross-linked chloromethyl precursor layer is contacted with a 20-35 wt% trimethylamine aqueous solution and reacted at 20-40°C for 2-12 hours. C2. Wash with deionized water until the pH of the washing solution on the membrane surface is 6-8; C3. Dry at 30-60℃ for 1-6 hours to obtain the anion exchange active layer with a water content of 10-45wt%, an ion exchange capacity of 0.8-1.8mmol / g and a thickness of 0.3-1.5μm based on a two-layer composite dry membrane consisting of a PVDF porous support layer and a cross-linked quaternized aromatic polymer layer.
6. The recycling method according to claim 2, characterized in that, The zirconium phosphate selective interface layer is prepared by the following steps: D1. Contact the outer surface of the anion exchange active layer with an aqueous solution of zirconium oxychloride octahydrate with a concentration of 0.02-0.20 mol / L for 1-15 min in a one-sided contact manner; D2. Then, the outer surface is brought into contact with a 0.05-0.50 mol / L phosphoric acid aqueous solution for 5-60 minutes in a single-sided contact manner; D3. Wash with deionized water and dry at 25-50℃ for 0.5-4h to obtain the zirconium phosphate selective interface layer with a loading of 0.05-0.50mg / cm², a thickness of 20-120nm, and a Zr / P atomic ratio of 0.6-1.
4.
7. The iron-containing nitric acid waste liquid according to claim 1, characterized in that, At least one of the following conditions must be met: The dissolved iron ions include Fe 3+ and Fe 2+ And Fe calculated as Fe 3+ Concentration greater than Fe based on Fe 2+ concentration; The iron-containing nitric acid waste liquid originates from the stainless steel pickling process or the metal chemical polishing process.
8. The recycling method according to claim 2, characterized in that, Include at least one of the following operations: In step S1, the iron-containing nitric acid waste liquid undergoes solid-liquid separation before entering the diffusion dialysis unit. The solid-liquid separation is performed using filtration with a pore size of 1-50 μm, and the suspended solids content in the feed liquid after filtration is less than 1 wt%. In step S3, the feed liquid and the receiving liquid pass through the diffusion dialysis unit in a countercurrent manner, and the linear velocities on both sides are 0.03-0.12 m / s.
9. The recycling method according to claim 2, characterized in that, The recovered acid solution contains 5-20 wt% free nitric acid and a total iron concentration (calculated as Fe) of no more than 10 g / L.
10. The recycling method according to claim 2, characterized in that, After continuous operation for 8-72 hours, the diffusion dialysis unit is flushed online for 0.2-2 hours with deionized water or a nitric acid aqueous solution with a mass fraction of 0.1-5.0 wt%.
Citation Information
Patent Citations
Device and method for recovering waste acids from acid pickling of steel through diffusion dialysis
CN110776139A
Method for recovering nitric acid / hydrofluoric acid from stainless steel pickling waste liquid
CN117964063A